International Business / Competing in the Global Marketplace - Hill W. Charles (Mcgraw Hill Irwin, 2012)
Introduction and Overview, Country Differences, The Global Trade and Investment Environment, The Global Monetary System, The Strategy and Structure of International Business, Business Operations, Glossary, Photo Credits, Index.